If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16e + 6 = 8e + -12 Reorder the terms: 6 + 16e = 8e + -12 Reorder the terms: 6 + 16e = -12 + 8e Solving 6 + 16e = -12 + 8e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-8e' to each side of the equation. 6 + 16e + -8e = -12 + 8e + -8e Combine like terms: 16e + -8e = 8e 6 + 8e = -12 + 8e + -8e Combine like terms: 8e + -8e = 0 6 + 8e = -12 + 0 6 + 8e = -12 Add '-6' to each side of the equation. 6 + -6 + 8e = -12 + -6 Combine like terms: 6 + -6 = 0 0 + 8e = -12 + -6 8e = -12 + -6 Combine like terms: -12 + -6 = -18 8e = -18 Divide each side by '8'. e = -2.25 Simplifying e = -2.25
| 4e+8=2e-15 | | (3x-8)(4x+9)= | | -6+4(11-5m)= | | 7p-1=5p+11 | | 3y-y-8y= | | 3x-7=7-4x | | 3x+4x+5x-2x=4x+5x+20 | | 9x-7=8x-1 | | 2x^3+9x^2+4x+6=0 | | 4x-3y+5x-2y= | | 2x^3-9x^2+4x+6=0 | | 8*10+10y=80 | | =2(3b+5)+4(2b-3) | | 4x^2+5k=(5k+1)x | | 13x-49=7x+29 | | =3(a+2b)-3b | | 2+cosx=0 | | 2+2cosx=0 | | x^2=18y^2-y^4 | | 8ab+12ab-12a= | | 7(h+1)=3+7h | | 3(g-1)=-2(2+g) | | 36x^2y^3+xy^2= | | =b(b+3)-2 | | =6(a+3)+2 | | =8a+2(5-b)-2a | | 6x^3+4x^2-14x+4=0 | | 125r^2-45= | | 3(2d+3)=12 | | 12r^2-75= | | =13a-b+3-6a+b | | 18.50+d=26.5 |